2015
DOI: 10.1007/s10103-015-1737-2
|View full text |Cite
|
Sign up to set email alerts
|

Corneal cut closure using temperature-controlled CO2 laser soldering system

Abstract: We aimed to evaluate the effectiveness of temperature-controlled laser soldering for repair of large perforated corneas in a porcine model. Eight Yorkshire pigs aged 6 months underwent 6-mm-deep 180° crescent-shaped trephination of the central corneas. Right corneal injuries were repaired by placement of 47 % bovine albumin along the cut followed by CO2 laser soldering (power density 16 W/cm(2)) to a target temperature of 65(°). Left corneal injuries were repaired with 10/0 nylon sutures. The groups were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Recently, the effective application of temperature control and radiometry during laser soldering to treat corneal cuts has been reported [132,133]. For example, Tal et al demonstrated the application of a temperature-controlled CO 2 laser soldering system (power density of 16 W/cm 2 ; 65°C) using a BSA-based solder (47%) for corneal cut closure [132]. The authors used pigs as the animal model and demonstrated that the soldered corneas had milder stromal inflammation, less neovascularization, and a higher level of re-epithelization than sutured controls.…”
Section: Serum Albumin-based Adhesivementioning
confidence: 99%
“…Recently, the effective application of temperature control and radiometry during laser soldering to treat corneal cuts has been reported [132,133]. For example, Tal et al demonstrated the application of a temperature-controlled CO 2 laser soldering system (power density of 16 W/cm 2 ; 65°C) using a BSA-based solder (47%) for corneal cut closure [132]. The authors used pigs as the animal model and demonstrated that the soldered corneas had milder stromal inflammation, less neovascularization, and a higher level of re-epithelization than sutured controls.…”
Section: Serum Albumin-based Adhesivementioning
confidence: 99%
“…Corneal inflammation remains a major and common clinical problem underlying many disease processes, such as: severe dry eye, infectious keratitis, chemical burn related injuries, corneal graft rejection and others [16]. If left untreated at its initial stages, corneal inflammation often progresses to a chronic stage and this persistent infiltration of the cornea by white blood cells and macrophages may lead to neovascularization, corneal opacity, edema, and vision loss [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[67] Others have developed elegant infraredbased CO 2 lasers for tissue soldering. [68][69][70] Combining tissue soldering technology with CaproGlu may open more avenues of application for tissue fixation.…”
Section: Discussionmentioning
confidence: 99%